2020
DOI: 10.3354/ab00724
|View full text |Cite
|
Sign up to set email alerts
|

Assigning functional feeding groups to aquatic arthropods in a Neotropical mountain river

Abstract: The importance of aquatic arthropods in the processing of organic matter in fluvial systems is well known, but this topic has been poorly studied in Neotropical rivers. In this research, we studied the composition of functional feeding groups (FFGs) associated with differences in elevation in a tropical river in northern Colombia during the wet and dry seasons. Between 2008 and 2013, we collected benthic arthropods at 3 sites located in the upper (San Lorenzo), intermediate (La Victoria) and lower (Puerto Mosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
1
0
3
Order By: Relevance
“…Estos y muchos otros trabajos se suman al inventario mundial de Elmidae y proporcionan valiosa información acerca de la diversidad y distribución de estos escarabajos acuáticos. En Colombia los estudios publicados en las últimas décadas involucran principalmente trabajos ecológicos (Posada, et al, 2000;Arango, et al, 2008;Longo-Sánchez, et al, 2009;Parra-Trujillo, et al, 2010;Duque, et al, 2012;Meza-S, et al, 2012;Zúñiga, et al, 2013, Villada-Bedoya, et al, 2017Lozano-Bravo, et al, 2018;Tamaris-Turizo, et al, 2020), en tanto que los trabajos de evaluación de la calidad de agua o de consultoría ambiental traen información de circulación restringida y hacen parte de la llamada "literatura gris". En algunos casos las determinaciones requieren un mayor rigor taxonómico o la confirmación con especialistas (Sondermann, 2013), de allí la importancia del estudio de los élmidos en Colombia.…”
Section: Introductionunclassified
“…Estos y muchos otros trabajos se suman al inventario mundial de Elmidae y proporcionan valiosa información acerca de la diversidad y distribución de estos escarabajos acuáticos. En Colombia los estudios publicados en las últimas décadas involucran principalmente trabajos ecológicos (Posada, et al, 2000;Arango, et al, 2008;Longo-Sánchez, et al, 2009;Parra-Trujillo, et al, 2010;Duque, et al, 2012;Meza-S, et al, 2012;Zúñiga, et al, 2013, Villada-Bedoya, et al, 2017Lozano-Bravo, et al, 2018;Tamaris-Turizo, et al, 2020), en tanto que los trabajos de evaluación de la calidad de agua o de consultoría ambiental traen información de circulación restringida y hacen parte de la llamada "literatura gris". En algunos casos las determinaciones requieren un mayor rigor taxonómico o la confirmación con especialistas (Sondermann, 2013), de allí la importancia del estudio de los élmidos en Colombia.…”
Section: Introductionunclassified
“…Por otra parte, Córdoba-Ariza et al (2020) describieron la estructura trófica en tres ríos de la Guayana colombiana. De igual manera, en un estudio elaborado por Rodríguez-Barrios et al (2011) se realizó una caracterización de los grupos funcionales alimentarios en el río Gaira en la región Caribe, que luego fue complementada por Tamaris-Turizo et al (2020). En general, estas contribuciones muestran que existe una amplia variabilidad en la utilización de recursos entre los macroinvertebrados acuáticos.…”
Section: Introductionunclassified
“…En general, estas contribuciones muestran que existe una amplia variabilidad en la utilización de recursos entre los macroinvertebrados acuáticos. De hecho, es frecuente encontrar una alta plasticidad dentro de un mismo grupo taxonómico (p.e., dentro de la familia Hydropsychidae, Tamaris-Turizo et al, 2020).…”
Section: Introductionunclassified
“…This genus of aquatic insects is widely distributed in the streams of South America, and its larvae are considered to be typical leaf shredders, using leaves not only for their nutrients, but also as the raw material for the construction of their cases (Wantzen & Wagner, 2006). However, research suggest that Phylloicus larvae have shown plasticity in their dietary behavior (Ferreira et al, 2015;Tamaris-Turizo et al, 2020). Therefore, the present study considered the developmental instar of the larvae, the season (dry or rainy), and the relationship between the larvae and the substrate for the evaluation of dietary patterns contributing to the dataset on their trophic ecology and feeding behavior in tropical streams.…”
Section: Introductionmentioning
confidence: 99%